EMERGENCY TRACHEOSTOMY, AN EXPERIENCE OF 120 CASSES: Emergency Tracheostomy - Najam, Maj Atif; Manzoor, Tahir; Qayum, Asad (Pakistan Armed Forces Medical Journal, 2010)
Objectives: The objective of this study is to compare short term complications in elective and emergency tracheostomyStudy Design: Qausi Experimental studyPlace and Duration of Study: Department of ENT, Head and Neck Surgery Combined Military Hospital Rawalpindi from Jun 2006 to Jun 2008.Patients and Method: In this study 120 patients undergoing tracheostomy were included. Patients were purposely divided into two groups of 60 each. Patients in Group A had elective tracheostomy where as group B included 60 patients who under went emergency tracheostomy. Short term complications including haemorrhage, surgical emphysema, cardiac arrest and stomal infection were noted in both groups. Chi-square test was applied as test of significance to compare the two groups.Results: Emergency tracheostomy in our study is associated with significantly increased risk of haemorrhage and surgical emphysema (p value being